Good Corporate Governance and Tax Avoidance in IDX Property Firms - Louise Henrik Saputra Malau; Elen Puspitasari (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes how corporate governance mechanisms – specifically the Audit Committee, Independent Board of Commisioners, and Institutional Ownership – affect tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX). Methodology/approach: The analysis uses 48 firm-year observations derived from secondary data collected from the annual reports of 12 real estate and property businesses between 2021 and 2024. The Effective Tax Rate (ETR) is used to measure tax avoidance, and multiple linear regression is used to evaluate the data. Results/findings: The findings indicate that Independent Board of Commisioners and Institutional Ownership do not significantly influence tax avoidance. In contrast, the Audit Committee has a significant negatove effect, demonstrating that stronger audit oversight reduces tax avoidance practices. These resluts confirm that audit monitoring plays a critical role in strengthening tax compliance. Conclusions: The study concludes that the effectiveness of corporate governance in limiting tax avoidance depends primarily on the strength and effectiveness of the Audit Committee rather than board independence or ownership structure. Limitations: This analysis is limited to property and real estate companies listed on the IDX during 2021 – 2024 period. Contributions: This study provides empirical evidence highlighting the central role of audit committees in reducing tax avoidance, particularly within the property and real estate sector. The findings contribute to the corporate governance and taxation literature and offer practical implications for strengthening governance mechanisms to improve tax compliance.